Technology, Power and Society : Critical Perspectives on the Global Digital Transformation - Mutsvairo, Bruce; Nguyen, Dennis; Zeng, Jing (Social Sciences E-Books Online, Collection 2025., 2025)
Technology, Power and Society: Critical Perspectives on the Global Digital Transformation offers a critical exploration of how digitalization, datafication, and automation impact societies worldwide, with a particular focus on underrepresented and understudied contexts. This interdisciplinary volume unpacks the sociopolitical dynamics of new technologies, investigating their potential to empower, disrupt, and transform social structures across varied cultural landscapes. The book takes a broad view at various critical issues pertaining to digital media technologies and the socio-cultural challenges that come with their rise: How do big tech platforms try to dominate Internet access in the Global South? To what extent can they offer ways for resistance, where do they post risks for activists? How do current technology discourses maintain gender stereotypes and imbalances? How do visions of AI differ between political cultures? And how can we develop methodologies capable of capturing the complexity of global technology trends and their local manifestations? By bringing together global perspectives, this collection moves beyond conventional narratives to foster a nuanced understanding of how digital transformations both challenge and reshape local contexts.